ANALISIS KESULITAN PESERTA DIDIK DAN FAKTOR-FAKTOR PENYEBABNYA PADA MATERI LUAS PERMUKAAN KERUCUT DAN TABUNG - Hapsari, Zihan Marcela; Dedi Muhtadi; Sukirwan (Universitas Islam Nusantara, 2024)
The purpose of this study is to analyze students' difficulties in solving the surface area problem of cones and tubes and the factors that cause them. The research subjects consisted of 32 seventh grade learners in a public junior high school in Tasikmalaya City. The research instruments included tests to identify learners' difficulties and in-depth interviews with some learners to gain further insight into the factors causing difficulties. The results showed that most of the students had difficulties in understanding the basic concepts of three-dimensional geometry, especially in applying the formula for the area of cones and pipes. Common difficulties found included an inability to recognize the elements of cones and tubes, difficulty substituting values in the formula, and obstacles in basic algebra that affect the final calculation results. Further analysis revealed that factors contributing to these difficulties included a lack of visualization skills and spatial understanding. Discussion of the results highlighted the importance of a more interactive and contextualized approach to learning, including the use of visual aids and manipulatives to help students visualize three-dimensional shapes and better understand the concept of surface area. The implications of this study include improving the curriculum and teaching strategies for mathematics at the junior secondary level, with a focus on developing learners' visualization skills and spatial understanding.